The formation and degradation of active species during methanol conversion over protonated zeotype catalysts. (17th July 2015) - Olsbye, U.; Svelle, S.; Lillerud, K. P.; Wei, Z. H.; Chen, Y. Y.; Li, J. F.; Wang, J. G.; Fan, W. B.
Abstract : Studies leading to the current understanding of the initial and final stages of the methanol to hydrocarbon (MTH) reaction are reviewed. Abstract : The methanol to hydrocarbon (MTH) process provides an efficient route for the conversion of carbon-based feedstocks into olefins, aromatics and gasoline. Still, there is room for improvements in product selectivity and catalytic stability. This task calls for a fundamental understanding of the formation, catalytic mechanism and degradation of active sites. The autocatalytic feature of the MTH process implies that hydrocarbons are active species on the one hand and deactivating species on the other hand. The steady-state performance of such species has been thoroughly studied and reviewed. However, the mechanism of formation of the initial hydrocarbon species ( i.e. ; the first C–C bond) and the evolution of active species into deactivating coke species have received less attention. Therefore, this review focuses on the significant progress recently achieved in these two stages by a combination of theoretical calculations, model studies, operando spectroscopy and catalytic tests.